Low Evapotranspiration Enhances the Resilience of Peatland Carbon Stocks to Fire. Issue 18 (22nd September 2017) - Kettridge, N.; Lukenbach, M. C.; Hokanson, K. J.; Hopkinson, C.; Devito, K. J.; Petrone, R. M.; Mendoza, C. A.; Waddington, J. M.
Abstract: Boreal peatlands may be vulnerable to projected changes in the wildfire regime under future climates. Extreme drying during the sensitive postfire period may exceed peatland ecohydrological resilience, triggering long‐term degradation of these globally significant carbon stocks. Despite these concerns, we show low peatland evapotranspiration at both the plot‐ and landscape‐scale postfire, in water‐limited peatlands dominated by feather moss that are ubiquitous across continental western Canada. Low postfire evapotranspiration enhances the resilience of carbon stocks in such peatlands to wildfire disturbance and reinforces their function as a regional source of water. Near‐surface water repellency may provide an important, previously unexplored, regulator of peatland evapotranspiration that can induce low evapotranspiration in the initial postfire years by restricting the supply of water to the peat surface. Key Points: Evapotranspiration from feather moss peatlands is low following wildfire Low evapotranspiration is identified at the landscape scale through the observation of concomitant high surface temperatures Water repellency may act as an important, previously unidentified, control on peatland water loss via evaporation